Material development : adding value to wool waste through innovative design : an exegesis presented in partial fulfilment of the requirement for the degree of Master of Design, Massey University, Wellington, New Zealand - Hutchinson, Hannah (Massey University, 2015)
Classic Sheepskins have found themselves with a challenging problem faced by similar companies; how best to be utilizing waste material generated during their production process. This research project employs design and technology to add value to waste wool fibres retrieved through the manufacturing process of sheepskin tanning. It is supported through a Callaghan Innovation fellowship with Classic Sheepskins, a Napier based tannery. They have been in business for over 40 years and provide high-quality natural New Zealand products and custom tanning. The focus of this research is to find innovative solutions for the wool waste, through material-responsive and industry- centered design methodologies and experimentation,. A critical position has been developed within sustainability, with concepts of traceability and authenticity also being examined. Consultation with Classic Sheepskins, and on-going evaluation of material properties and aesthetics in regards to potential applications, has determined the direction of products and end-outcomes.
Keywords: Wool waste; Recycling; Sustainable design